2014
DOI: 10.2337/dc13-2291
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Withdrawal, Placebo-Controlled Study Evaluating the Efficacy and Tolerability of Tapentadol Extended Release in Patients With Chronic Painful Diabetic Peripheral Neuropathy

Abstract: OBJECTIVEThis study evaluated the efficacy and tolerability of tapentadol extended release (ER) for the management of chronic pain associated with diabetic peripheral neuropathy (DPN). RESEARCH DESIGN AND METHODSAdults with moderate to severe DPN pain were titrated to tapentadol ER 100-250 mg bid during a 3-week open-label period; patients with ‡1-point reduction in pain intensity (11-point numerical rating scale) at end of titration were randomized to receive placebo or tapentadol ER (optimal dose from titrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(145 citation statements)
references
References 32 publications
5
133
1
5
Order By: Relevance
“…This finding contrasts the results of several controlled randomized trials in which tapentadol was reported to significantly reduce spontaneous pain in different acute and chronic pain syndromes, including chronic low back pain with a neuropathic component and painful diabetic neuropathy [13,26,27] . Tapentadol (immediate release) in comparison to placebo was able to reduce laserevoked potential responses and spontaneous pain in healthy volunteers using the UVB and topical capsaicin model within a randomized trial [28] .…”
Section: Discussioncontrasting
confidence: 99%
“…This finding contrasts the results of several controlled randomized trials in which tapentadol was reported to significantly reduce spontaneous pain in different acute and chronic pain syndromes, including chronic low back pain with a neuropathic component and painful diabetic neuropathy [13,26,27] . Tapentadol (immediate release) in comparison to placebo was able to reduce laserevoked potential responses and spontaneous pain in healthy volunteers using the UVB and topical capsaicin model within a randomized trial [28] .…”
Section: Discussioncontrasting
confidence: 99%
“…Tapentadol extended release is a novel centrally acting opioid analgesic that exerts its analgesic effects through both m-opioid receptor agonism and noradrenaline reuptake inhibition. Extended-release tapentadol was approved by the FDA for the treatment of neuropathic pain associated with diabetes based on data from two multicenter randomized withdrawal, placebocontrolled phase 3 trials (103,104). However, both used an enriched design and therefore are not generalizable, and a recent systematic review and meta-analysis by the International Association for the Study of Pain Special Interest Group on Neuropathic Pain (NeuPSIG) found the evidence of the effectiveness of tapentadol in reducing neuropathic pain inconclusive (15).…”
Section: Approved Medicationsmentioning
confidence: 99%
“…About 1/3 of all patients with DM suffer from diabetic neuropathic pain [6] and moreover, it has a huge impact on the quality of life (QoL) of the person [8][9][10]. There are several trials which have reported some benefit in the improvement of symptoms of PDN with various antidepressants, anticonvulsants, opioid and topical medications [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The follow up studies reported that only 23% patients had satisfactory improvement of symptoms of PDN after conventional treatment [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…A met analysis on efficacy on antidepressants and anticonvulsants in combination or alone showed up to 50% reduction in pain [24]. Trial with newer medication such as tapentadol which possesses dual mode of action, opioid agonists and norepinephrine uptake inhibitor show some improvement in painful diabetic neuropathy [25]. Apart from oral treatment, there are trials with some efficacy in treating PDN with topical agents including capsaicin [26] and also isosoribide mononitrate spray [27].…”
Section: Introductionmentioning
confidence: 99%